PERAN BUDAYA ORGANISASI DALAM MEMEDIASI PELATIHAN KERJA, KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI RUMAH SAKIT KENARI GRAHA MEDIKA CILEUNGSI -BOGOR - Rahmanullah, Farzaher; Hamid, Abdul; Zuswana, Aries (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
This study aims to analyze the influence of job training, leadership, and job satisfaction on employee performance, both directly and through organizational culture as a mediating variable. The research used a quantitative approach with path analysis and Sobel test. The results indicate that job training (p = 0.487) and job satisfaction (p = 0.840) do not have a significant direct effect on employee performance. Conversely, leadership has a positive and significant effect on performance (p = 0.003). Organizational culture also shows a significant positive effect on performance (p = 0.000). Indirectly, job training, leadership, and job satisfaction significantly influence employee performance through organizational culture, as evidenced by the Sobel test (z > 1.65 and p < 0.05). These findings demonstrate that organizational culture plays a strong mediating role, functioning as a full mediator (in the relationship between training and job satisfaction with performance) and as a partial mediator (in the relationship between leadership and performance). The study emphasizes the importance of building a strong organizational culture to enhance the impact of training, leadership, and job satisfaction on employee performance.